2020
DOI: 10.1186/s12884-020-03075-8
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of planning a vaginal birth after caesarean in different models of maternity care in Australia

Abstract: Background: Vaginal birth after caesarean (VBAC) is a safe mode of birth for most women but internationally VBAC rates remain low. In Australia women planning a VBAC may experience different models of care including continuity of care (CoC). There are a limited number of studies exploring the impact and influence of CoC on women's experiences of planning a VBAC. Continuity of care (CoC) with a midwife has been found to increase spontaneous vaginal birth and decrease some interventions. Women planning a VBAC pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 65 publications
3
34
1
Order By: Relevance
“…The study's focus on health equity in maternal health corresponds to the latest priorities of the US Surgeon General and Department of Health and Human Services 48,49 . Although the experiences of our participants occurred during a global health crisis, their mean scores on the MADM and MOR were slightly higher than in a comparable pre‐COVID‐19 US national sample, 39 and median scores were higher than pre‐COVID‐19 Australian and German samples 50,51 …”
Section: Discussioncontrasting
confidence: 58%
“…The study's focus on health equity in maternal health corresponds to the latest priorities of the US Surgeon General and Department of Health and Human Services 48,49 . Although the experiences of our participants occurred during a global health crisis, their mean scores on the MADM and MOR were slightly higher than in a comparable pre‐COVID‐19 US national sample, 39 and median scores were higher than pre‐COVID‐19 Australian and German samples 50,51 …”
Section: Discussioncontrasting
confidence: 58%
“…Vedam and colleagues found that improved access to midwives was associated with higher rates of VBAC and lower rates of cesarean in the United States 55 . Similarly, a continuity of care model of care, common in midwifery practices, has been shown to increase experiences of respect and autonomy 56 . Our sample trended in this direction; nearly 40% of participants who planned a VBAC had a midwife provider for their second birth, a rate that is significantly higher than the United States as a whole where only about 10% of people give birth with a midwife 57 .…”
Section: Discussionmentioning
confidence: 99%
“…The survey development and pilot testing has previously been published [ 22 ]. The survey included 114 items that contained demographic, yes/no, Likert scales, open ended questions and validated tools grouped around the four factors.…”
Section: Methodsmentioning
confidence: 99%
“…The qualitative findings were integrated into the next phase of the study which was a national survey. The quantitative results of the experiences of women who had planned a VBAC in the previous five years in different models of maternity care has been published [ 22 ]. The aim of this paper is to explore the nature and impact of the interactions between women planning a VBAC and health care providers from women’s perspectives.…”
Section: Introductionmentioning
confidence: 99%